THE RECENT GROWTH OF E-COMMERCE IN INDIA: A CASE STUDY ON ZOMATO, SWIGGY, OLA, AND OTHER SUCCESSFUL CORPORATES (International Journal of Food and Nutritional Sciences, 2022)
The Indian e-commerce market has witnessed explosive growth in recent years, driven by digital transformation, increased internet penetration, and changing consumer behavior. Companies like Zomato, Swiggy, and Ola have become prominent players in reshaping the way services and products are delivered. This paper explores the rapid development and success of e-commerce platforms in India, analyzing the factors behind their growth, their economic impact, and the challenges they face moving forward. It offers a comprehensive understanding of how these companies are contributing to India’s digital economy.